Perancangan dan Pembangunan Taman Apotek Hidup pada Lanskap Industri, Kabupaten Kudus - Alfred Jansen Sutrisno; Hermanto (http://arl.faperta.ipb.ac.id/, 2020)
Gardener in the industrial landscape has limited knowledge and experience in managing the environment. Meanwhile, there are areas in the industrial landscape that can be developed into thematic parks. The purpose of this activity is to train gardener in designing and constructing parks that have good visual quality. The living pharmacy park is a concept park that is trying to be developed. This park is dominated by a collection of medicinal plants or often also called the family medicinal plant garden (Tanaman Obat Keluarga - TOGA). The method used are a workshop and Focus Group Discussion (FGD). The area of land that is used as a place for design and construction activities is 720.3 m2. The design process starts from an inventory of existing conditions, then analyzed and synthesized to get the appropriate park design. After the design results were agreed upon, a park was developed. Park development must be in accordance with the results of the design. However, the obstacle faced is that there are some problems that are not properly inventoried and found during development. Even though, the results of the construction of the park are still quite in accordance with the results of the design. Keywords: Gardener, Living Pharmacy Park, Medicinal Plant, Visual Quality